Gamification and ESL Learning: Enhancing Language Skills through Literary-Themed Escape Room Activities - Azmi, Fairuz Umira; Navarathnaraja, Kirooshini; Mohd Ali, Siti Munirah; Hanim Ismail, Hanita (Forum for Linguistic Studies, 2025)
This study investigates how the LitEscape Challenge, a gamified literary escape-room activity, enhances ESL students' understanding of key narrative elements, such as plot, character, setting, theme, conflict, and moral values, while simultaneously promoting a deeper engagement with the linguistic structures found in literary texts. The activity was conceptualized to provide a problem-based learning environment where students work collaboratively to progress through stages by decoding the literary clues. Grounded in behaviourist, constructivist, and engagement theories, the intervention was carried out over four weeks with 30 Form 5 students in Malaysia. Utilising a quasi-experimental, mixed-methods design, learning outcomes were assessed through pre- and post-tests, supplemented by a thematic analysis of reflective writing. The results reveal significant improvements in literary comprehension (p < 0.001, d = 2.25), indicating a large effect size. Qualitative evidence further revealed an increase in learners' motivation, collaboration, critical thinking and heightened the metalinguistic awareness through active problem-solving, peer interaction and reflective engagement with the literary text. These findings suggest that when gamification is thoughtfully designed around linguistic objectives and narrative structures, it can improve both aesthetic appreciation and language competence in ESL literature instruction. This study presents practical implications for ESL teachers by offering a replicable, low-technology, game-based model that incorporates language-focused pedagogy to support meaningful, engaging and skill-oriented literature instruction.